Regional climate dividend provides relief to rural households, but hardship cases remain - Stefan Bach; Rebecca Engelhardt; Lars Felder; Peter Haan; Renke Schmacker (DIW Weekly Report, 2025)
The previous federal government coalition had planned to pay private households a climate dividend to offset rising carbon prices; a payout process was even prepared. However, the climate dividend is nowhere to be seen in the new federal government's coalition agreement. In the long term, a social compensation mechanism will be important, as prices for fossil and heating fuels will continue to rise due to the European Emissions Trading System (EU-ETS2). The simulations in this Weekly Report show that a climate dividend would contribute significantly to offsetting the financial burden from rising carbon prices, especially for low-earning households, while simultaneously maintaining the incentive of the price signal. Moreover, there are structural differences between urban and rural areas, which a regionally staggered climate dividend can account for. According to the present calculations, such staggering lowers the share of social hardship cases in rural areas, while increasing the share of them in cities. Although a regionally staggered climate dividend may not help to offset hardship cases overall, it could boost acceptance of carbon pricing in rural areas. To increase the targeted effect, the climate dividend could be reduced for higher incomes, which would open up additional fiscal leeway for relieving social hardship cases.
Keywords: Q41; D31; R28; 330; Carbon pricing; climate dividend; personal and regional redistribution